Synthesis and Characterization of Oxidized Starch-Montmorillonite Composite for Efficient Removal of Crystal Violet Dye from Aqueous Solutions - Van Hung Nguyen; Dang Khoa Vo Nguyen; Chi Nhan Ha Thuc (Journal of Technical Education Science, 2024)
An effective adsorbent was synthesized by modifying Montmorillonite (MMT) clay with oxidized starch, aiming to remove crystal violet (CV) dye from aqueous solutions. The chemical modifications in the MMT-oxidized starch composite were characterized using Fourier-transform infrared spectroscopy (FTIR), confirming the successful integration of oxidized starch with MMT. The adsorption performance was evaluated under varying conditions, including initial dye concentration, adsorbent dosage, pH, and contact time. Kinetic analysis revealed that the adsorption process followed a pseudo-second-order model, while equilibrium data were fitted by the Langmuir isotherm, indicating monolayer adsorption. The adsorbent demonstrated a high adsorption capacity of 25.4 mg/g at pH 7 for CV dye. Thermogravimetric analysis (TGA) confirmed the thermal stability of the synthesized material and these findings suggest that oxidized starch-MMT is a promising alternative for the efficient removal of cationic dyes like crystal violet from wastewater, with significant implications for scalable water treatment applications and broader environmental remediation efforts in both industrial and municipal settings.